2022
DOI: 10.1166/jbt.2022.2902
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal MicroRNA-325 Enhances Trophoblast Migration and Invasion Through Downregulation of Lethal-7b and Upregulation of Forkhead Box Protein O1 Expression in Preeclampsia

Abstract: We aimed to explore the mechanism by how microRNA (miRNA)-325 derived from marrow mesenchymal stem cell exosomes (MSC-exos) affects the trophoblast progression in preeclampsia (PE). RT-qPCR detected the level of miRNA let-7b and FOXO1 in the placenta tissue of PE patients. Functional experiment was performed to analyze the effect of FOXO1 inhibitor and let-7b mimics on cell migration, invasion and apoptosis through Transwell assay and TUNEL staining. The trophoblast cell was co-cultured with overexpressed-miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In conclusion, miR-325 derived from MSC-exosome stimulates FOXO1 upregulation and let7b inhibition to enhance trophoblast cell invasion and migration in PE. 155 A summary of the therapeutic utility of MSCs-exosome for PE therapy has been offered in Table 4.…”
Section: Msc-exosome-mediated Angiogenesis In Pementioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, miR-325 derived from MSC-exosome stimulates FOXO1 upregulation and let7b inhibition to enhance trophoblast cell invasion and migration in PE. 155 A summary of the therapeutic utility of MSCs-exosome for PE therapy has been offered in Table 4.…”
Section: Msc-exosome-mediated Angiogenesis In Pementioning
confidence: 99%
“…Human umbilical cord miR-139-5p ERK/MMP-2 Speed up trophoblast cell invasion and migration while inhibiting apoptosis [141] Amnion EZH2 mTOR Increased autophagy in hypoxic trophoblasts [146] Bone marrow miR-141 MALAT1-201 Controlled the migration, apoptosis, and proliferation of trophoblast cells [148] Human umbilical cord TFCP2 Wnt/β-catenin Enhances the growth dynamics and lowers EVT apoptosis [151] Human umbilical cord let-7b FOXO1 Targeting AKT signaling pathway [154] Bone marrow miR-325 FOXO1 Trophoblast cell invasion and migration [155] Abbreviations: EZH2, enhancer of zeste homolog 2; FOXO1, forkhead box O1; FSTL3, follistatin-like 3; MMP-2, matrix metalloproteinase-2; PDCD4, programmed cell death 4; sFlt-1, soluble fms-like tyrosine kinase-1; SCG2, secretogranin II; TFCP2, transcription factor cellular promoter 2; TFPI2, tissue factor pathway inhibitor 2; VEGF, vascular endothelial growth factor. Attempts to establish guidelines regarding the safety and efficacy of exosome therapy will hasten clinical utilization of MSC-derived exosomes as an intriguing therapeutic for PE.…”
Section: Cell Source Enriched Molecule Target Involved Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of miR-let-7b within MSC-Exos have been documented, indicating a prospective role in regulating TLR4-mediated responses. 73,74 Studies have indicated that miR-199a-5p has the ability to target TLR4 and diminish its expression. MSC-Exos harboring this particular miRNA could influence TLR4 signaling and the resultant immune response.…”
Section: Referencesmentioning
confidence: 99%
“…MiR‐let‐7b is recognized for its capacity to target TLR4 and curtail its expression. The presence of miR‐let‐7b within MSC‐Exos have been documented, indicating a prospective role in regulating TLR4‐mediated responses 73,74 …”
Section: Regulation Of Prrs By Mscs‐derived Exosomesmentioning
confidence: 99%